The job quality of young higher education graduates in Portugal: Wage differentials and contractual arrangements in 2007 and 2012 - Suleman, F.; Figueiredo, M. C. T. (Workshop DINAMIA'CET, 2017)
This article explores the wage differentials among young graduates engaged in different contractual arrangements. We use linked employer-employee data – “Quadros de Pessoal”, for 2007 and 2012, to examine the quality of jobs of young under and master graduates in Portugal. The time frame allows us not only to explore the job quality but also to control the effect of the 2008 crisis. The empirical analysis focuses on the impact of flexibility (stability) and full (part) working time on wages. More specifically, this study examines the impact of five types of contractual arrangements, notably Standard (stable and full-time), Underemployed (stable and part-time), Insecure (flexible and full-time), Non-Standard (flexible and part-time) and others that include very short-time or on-call contracts. We labelled them as Mini-jobs. Few studies have examined multiple dimensions of contracts. It is thus possible to determine whether the combination of flexible (stable) contracts and full (part) working time and Mini jobs correlate with lower (higher) wages. However, it is argued that education, workers, and firms’ characteristics shape inequality and wage differentials among young graduates. The model includes a set of control variables notably a proxy of time of graduation, field of education, gender, migration status, tenure, occupation, internship status, firm size, industry affiliation, and regional distribution. Estimation strategy adopts the treatment effect model to deal with imprecise and inconsistent estimates arising from the OLS earnings model. It is assumed that graduates themselves can select, or at least accept, the contractual arrangement; therefore we use a treatment-outcome model for multinomial choice of contractual arrangements. The results show that graduates faced a wage drop between 2007 and 2012. The evidence related to the impact of four types of contract indicates that stability benefits graduates whether they have full- or part-time contract. The flexible contracts impact wages differently: Mini-jobs and Non-standard contracts impose the largest penalisation in the labour market. There are however differences between 2007 and 2012. In 2007, graduates benefit from Non-Standard contracts since graduates in flexible and part-time jobs earn a wage premium, while in 2012, that type of contract imposes a penalisation. This indicates that probably the composition of graduates vary among non-standard jobs. Furthermore, the penalisation is higher for ‘Bologna undergraduates’. Our findings corroborate previous research in that ‘Bologna undergraduates’ earn lower wages and are more probable in non-standard contracts. The data from 2012 show in addition that ‘non-Bologna graduates’ benefit from wage premium, are protected in the labour market and are immune to the expansion of higher education. The findings evidence a segmentation of the labour market of young higher education graduates. Furthermore, they show also a ranking of generations of graduates and suggest that ‘Bologna undergraduates’ face the lowest job quality. This result leads us to question the rationale of the expansion of higher education and the Bologna reform, which attempted to increase job opportunities and access to high quality jobs,especially for underprivileged categories of young.